MITIGATION MODEL DEVELOPMENT AND DROUGHT EFFECT ANTICIPATION AT TRENGGALEK REGENCY - Waspodo, Roh Santoso Budi; Dewi, Vita Ayu Kusuma; Pratama, Galih Bhekti Sula (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2019)
The farm is an important sector that affects economic growth. El-Nino and La-Nina climate anomalies have an impact on the farm such as drought. Actions to overcome the limiting factors on marginal land need to be done through technologies application on soil conservation and water management, balanced soil nutrient management and a better understanding of climate anomalies. Therefore, mitigation models development and anticipation of the effects of drought need to be carried out to provide an alternative technology. The research stages was biophysical conditions analysis, hydrological and geological data analysis, and formulation of drought mitigation technology. Based on the research, there is a drought potential that needs to be anticipated. Technology that could be applied are water reservoirs, dykes, infiltration canals, rorak, slot mulch, and reservoir. Soil and water conservation technology can increase groundwater. Method that have a significant impact is making embankments with mulch, which can increase the soil water content up to 56%. Keywords: Drought, Farm, Groundwater, Trenggalek